Bibliometric Analysis of Green Technology Research Trends and Their Impact on the Global - Judijanto, Loso; Suhara, Ade; Mayasari, Nanny (Westscience Press, 2024)
Green technology has emerged as a critical field of research due to growing global concerns about climate change and environmental degradation. This study conducts a bibliometric analysis to explore research trends in green technology and their impact on the global economy. The analysis covers publications from 1981 to 2024 and reveals a significant increase in research output, particularly after 2000, driven by global efforts to promote sustainability. Key themes identified include green technology innovation, investment, green growth, and technical advancements in green chemistry and solvents. China and the United States lead in research output and international collaboration, highlighting the global nature of green technology research. However, challenges such as the high costs of green technology adoption and the need for more interdisciplinary research persist. This study concludes that while green technology research has made substantial progress, future efforts must focus on making these technologies more economically viable and accessible, particularly in developing regions.